TINGKAT KEMISKINAN ANAK DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI PROVINSI SULAWESI BARAT TAHUN 2010-2011 - , Sumaryati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to perform the calculation and analysis of the child poverty rate and the factors that influenced in West Sulawesi Province using data Susenas 2010 and 2011. Children who grow up in poverty are tend to be poor in adulthood as well. Measuring child poverty is important because child poverty has its own causes and effects which are somewhat different from adult poverty. that used in this Multidimensional child poverty measurement methods study is to capture the true picture of child poverty. This study examined child poverty in five dimensions: education, health, sanitation and clean water, shelter and child labor. The method used to measure multidimensional child poverty is Alkire Foster method combined with the Bristol method. The measurement that used in this study is the headcount ratio, average poverty gap and adjusted headcount ratio. The results showed that the rate of child poverty (headcount ratio) in West Sulawesi Province in 2010-2011 is about 21 percent and the percentage of child poverty (adjusted headcount ratio) is still above 60 percent. Based on the value of average poverty gap, the average of all those children who are poor deprivased or have poor status on three indicators from thirteen child poverty indicators of child poverty. model The best to analyze the factors that affecting the child poverty in West Sulawesi Province in 2010 is a probit model while for 2011 is a logistic regression model. The results of probit analysis showed that the variable of household headâs gender, household headâs education level attained, the status of area of residence, the age of household head, and expenditures per capita in a month were the factors that affect child poverty. The results of logistic regression analysis showed that the factors that affecting child poverty in West Sulawesi Province in 2011 was the household headâs education level attained, the status of area of residence, the age of household head, and the expenditure per capita per month.